Effect of plant growth substances on growth and flowering attributes of African marigold (Tagetes erecta Linn.) (Indian Journal of Arid Horticulture, 2025)
Floriculture is now emerging as an important ven- ture in the world, especially as a potential money spinner. Many flowers and ornamental plants grown for domestic as well as for export market provide more returns per unit area than other horticultural crops. Marigold (Tagetes sp.) is on annual flowers to cultivate easily and have wide adaptabil- ity to different soil and climatic conditions. It belongs to family Compositeae and native of India. It has a great eco- nomic potential for loose flower trade. It is especially used for making garland, decoration and induced in landscape plans due to its variable height and colour. Marigolds have also great medicinal importance i.e. leaf extract is good rem- edy for ear-ache and flower extract is used as blood purifier and against bleeding piles. Besides, it is also found impor- tant in controlling nematodes because, it produce thiophenes, which are naturally occurring biocides. Appli- cation of plant growth substances showed tremendous potential in modulating growth and related processes. They are considered bio-soft wards, which elicit rapid as well as long term responses in crop plants (Yadav et al., 1994 and Malik et al., 1996).
Keywords: ornamental; Compositeae; adaptabil; retention; transloca- tion; chlorophyll